A multicenter real‐life study on the multiple reasons for uncontrolled allergic rhinitis. Issue 10 (14th July 2021) - Van Bulck, Pauline; Cools, Leen; Soumya, Mysore S.; Nyembue, Dieudonné T.; Kabobo, Patricia; Zhang, Luo; Scadding, Glenis K.; Toskala, Elina; Fokkens, Wytske J.; Steelant, Brecht; Hellings, Peter W.
Abstract: Background: : Recent data show uncontrolled disease in 35% of allergic rhinitis (AR) patients on medical treatment. The reasons for uncontrolled disease can arbitrarily be divided into disease‐related, diagnosis‐related, treatment‐related, and patient‐related factors. However, the relative importance of these factors in uncontrolled disease remains speculative. This explorative study aimed at determining the factors causing uncontrolled AR on four different continents worldwide, identifying the most common reasons for uncontrolled disease in AR. Methods: : Patients with uncontrolled AR (n = 430) were asked to fill out a questionnaire and underwent a clinical examination at the outpatient clinic in five university outpatient clinics (Leuven [Belgium], Beijing [China], Kinshasa [Congo], Bangalore [India], and Philadelphia [US]). Two independent physicians evaluated the reason or multiple reasons for uncontrolled disease. The study was coordinated from the University Hospital of Leuven. Results: : In uncontrolled AR patients, 76% of patients showed two or more reasons for uncontrolled disease according to the physicians' evaluation. Disease‐related factors (64%) were considered most often the reason for uncontrolled disease, followed by treatment‐ (56%), patient‐ (54%), and diagnosis‐related (47%) factors. There is limited variability in observations across different centers worldwide. Conclusion: : We here define the multiple reasons for uncontrolled AR across different continents, with disease‐related factors being most frequently associated with uncontrolled disease. A better understanding of uncontrolled disease will guide us in defining strategies to improve AR care.